2022
DOI: 10.1002/jcp.30781
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A aggravates renal apoptosis and necroptosis in selenium‐deficient chickens via oxidative stress and PI3K/AKT pathway

Abstract: Bisphenol A (BPA) in the environment can have deleterious effects on humans and animals. BPA can exert nephrotoxicity by inducing oxidative stress. Selenium (Se) deficiency can specifically impair kidney tissues and additionally show a synergistic effect on the toxicity of several environmental chemicals. However, the toxic effects of BPA on the chicken kidney and whether Se deficiency produces synergistic effects on the toxicity of BPA remain poorly understood. Herein, we established BPA exposure models and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Chicken embryo kidney (CEK) cells were isolated from 18‐days‐old SPF chicken embryos (Harbin Veterinary Research Institute, CAAS) based on standard techniques 26 and CEK cells were cultured in M199 medium (Gibco, Grand Island, NY) supplemented with 10% fetal bovine serum (FBS) (Thermo Fisher Scientific, Waltham, MA) and 1% penicillin–streptomycin (Solarbio, Beijing, China) at 37°C with 5% CO 2 in a cell incubator. BPA (Sigma‐Aldrich, Saint Louis, MO) was dissolved in anhydrous ethanol (Solarbio, Beijing, China) for a concentration of 0.01 g/ml for in vivo analysis, and BPA was dissolved in DMSO (1000 μM, Solarbio, Beijing, China), and then diluted with M199 (150.0 nM) for in vitro analysis according to our previous study 27 . Na 2 SeO 3 with analytical reagent grade (Sigma‐Aldrich, Saint Louis, MO) was dissolved in M199 medium for a preparation concentration of 1000 nM in vitro studies, and Na 2 SeO 3 was dissolved in normal saline medium for a preparation concentration of 0.03 g/ml in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken embryo kidney (CEK) cells were isolated from 18‐days‐old SPF chicken embryos (Harbin Veterinary Research Institute, CAAS) based on standard techniques 26 and CEK cells were cultured in M199 medium (Gibco, Grand Island, NY) supplemented with 10% fetal bovine serum (FBS) (Thermo Fisher Scientific, Waltham, MA) and 1% penicillin–streptomycin (Solarbio, Beijing, China) at 37°C with 5% CO 2 in a cell incubator. BPA (Sigma‐Aldrich, Saint Louis, MO) was dissolved in anhydrous ethanol (Solarbio, Beijing, China) for a concentration of 0.01 g/ml for in vivo analysis, and BPA was dissolved in DMSO (1000 μM, Solarbio, Beijing, China), and then diluted with M199 (150.0 nM) for in vitro analysis according to our previous study 27 . Na 2 SeO 3 with analytical reagent grade (Sigma‐Aldrich, Saint Louis, MO) was dissolved in M199 medium for a preparation concentration of 1000 nM in vitro studies, and Na 2 SeO 3 was dissolved in normal saline medium for a preparation concentration of 0.03 g/ml in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…BPA (Sigma-Aldrich, Saint Louis, MO) was dissolved in anhydrous ethanol (Solarbio, Beijing, China) for a concentration of 0.01 g/ml for in vivo analysis, and BPA was dissolved in DMSO (1000 μM, Solarbio, Beijing, China), and then diluted with M199 (150.0 nM) for in vitro analysis according to our previous study. 27 Na 2 SeO 3 with analytical reagent grade (Sigma-Aldrich, Saint Louis, MO) was dissolved in M199 medium for a preparation concentration of 1000 nM in vitro studies, and Na 2 SeO 3 was dissolved in normal saline medium for a preparation concentration of 0.03 g/ml in vivo studies. AMPK, mTOR, p62, Beclin 1, and LC3 polyclonal antibodies were purchased from the Wanlei (Shenyang, China) or Abcam (London, England), β-actin monoclonal antibody and horseradish peroxidase (HRP)-labeled secondary antibodies were provided by Sigma (Sigma-Aldrich, Saint Louis, MO).…”
Section: Animals Cell Reagents and Antibodiesmentioning
confidence: 99%
“…BPA also activated the AMPK/mTOR (The 5′-adenosine monophosphate-activated protein kinase and mammalian target of rapamycin) signaling pathway, which triggers P62/Lc3/Beclin1 signaling, leading to the formation of autophagosomes and autolysosomes, and ultimately, stimulating autophagy in renal cells [ 166 , 167 ]. BPA exposure down-regulated the expression of PI3K (phosphatidylinositide 3-kinases) and AKT (protein kinase B) and activated the Bcl/Bax-Caspase 9-Caspase 3 (B-cell lymphoma/BCL2-Associated X-Caspase 9-Caspase 3) signaling pathways, leading to apoptosis and necrosis of renal cells [ 168 ]. Recent studies have shown that BPA-induced renal dysfunction was associated with ferriosis, which depends on ferritin phagocytosis, through the activation of AMPK-mTOR-ULK1 (Unc-51-like kinase 1) axis [ 169 ].…”
Section: Bisphenol Amentioning
confidence: 99%
“…Oral exposure to BPA caused severe intestinal injury, inhibited intestinal epithelial cell proliferation, promoted apoptosis, and disrupted the intestinal barrier function in mice . Additionally, research on the toxicological mechanism of BPA revealed that BPA exerted nephrotoxicity by inducing oxidative stress to promote apoptosis and necroptosis of chicken kidney cells . Exposure of bighead carp to BPA can cause DNA damage in isolated blood lymphocytes, brain, gills, liver, and kidney cells .…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, research on the toxicological mechanism of BPA revealed that BPA exerted nephrotoxicity by inducing oxidative stress to promote apoptosis and necroptosis of chicken kidney cells. 9 Exposure of bighead carp to BPA can cause DNA damage in isolated blood lymphocytes, brain, gills, liver, and kidney cells. 10 BPA also activated the ataxia telangiectasia mutated (ATM)-p53 signaling pathway, leading to cell cycle arrest in human fetal lung fibroblasts, affecting fetal lung development and maturation.…”
Section: Introductionmentioning
confidence: 99%